1992
DOI: 10.1088/0031-9155/37/1/014
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of female human breast tissue measured in vitro at 3.2 GHz

Abstract: Complex permittivities of in vitro diseased and undiseased human female breast tissues have been measured at 3.2 GHz using a resonant cavity technique. Ranges of dielectric properties and water contents of these tissues are presented. Experimental data are compared with models predicted from mixture equations. Measured permittivity data lie within limits set by two-phase mixture theory, but some conductivity data are in excess of those expected for a mixture of saline and protein. At any particular microwave f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
137
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(147 citation statements)
references
References 18 publications
8
137
1
1
Order By: Relevance
“…Furthermore, the estimations of dielectric properties in scenario (iii) also agreed well with previous ex vivo studies such as [37,38,40,42]. However, Haemmerich et al [43] observed a change in some dielectric parameters after excising tissue and attributed those changes to variations of temperature, tissue dehydration and ischemic effects.…”
Section: Dielectric Propertiessupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, the estimations of dielectric properties in scenario (iii) also agreed well with previous ex vivo studies such as [37,38,40,42]. However, Haemmerich et al [43] observed a change in some dielectric parameters after excising tissue and attributed those changes to variations of temperature, tissue dehydration and ischemic effects.…”
Section: Dielectric Propertiessupporting
confidence: 87%
“…• The dielectric data spanned a much greater range of values than those reported in previous studies, with the exception of Campbell and Land's study [38].…”
Section: Dielectric Propertiesmentioning
confidence: 71%
See 1 more Smart Citation
“…17 Initial results of microwave radar-based imaging have been presented [17][18][19][20][21][22][23] and approaches rely on a difference in the dielectric properties (Dk) of normal and malignant breast tissues. [24][25][26][27][28][29][30][31] The breast as an organ is unique in the human body in that basic structure consists of glandular tissue (high dielectric constant, high conductivity, and radioopaque) in a fat (low dielectric constant, low conductivity, and relatively radiolucent)-based matrix. Inclusions, such as a tumor, are also of high permittivity, enhanced by the angiogenic increase in vascularity, and cysts contain fluid, which also have very high permittivity.…”
Section: Introductionmentioning
confidence: 99%
“…The measured data is compared with the available literature data on normal, benign and malignant breast tissues [14] and is given in Table 1. Good agreement is observed.…”
Section: Resultsmentioning
confidence: 99%